2003
DOI: 10.1523/jneurosci.23-11-04549.2003
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 47 (Cx47)-Deficient Mice with Enhanced Green Fluorescent Protein Reporter Gene Reveal Predominant Oligodendrocytic Expression of Cx47 and Display Vacuolized Myelin in the CNS

Abstract: To further characterize the recently described gap junction gene connexin 47 (Cx47), we generated Cx47-null mice by replacing the Cx47 coding DNA with an enhanced green fluorescent protein (EGFP) reporter gene, which was thus placed under control of the endogenous Cx47 promoter. Homozygous mutant mice were fertile and showed no obvious morphological or behavioral abnormalities. Colocalization of EGFP fluorescence and immunofluorescence of cell marker proteins revealed that Cx47 was mainly expressed in oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
271
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(289 citation statements)
references
References 55 publications
15
271
0
3
Order By: Relevance
“…Also, because NAA appears at low micromolar levels in cerebrospinal fluid (Faull et al, 1999), this could represent another route of NAA clearance from brain. Finally, it is possible that NAA taken up from the extracellular space by astrocytes could be transferred to oligodendrocytes via specific gap junctions (connexons) composed of connexins Cx32 and Cx47 (Menichella et al, 2003;Odermatt et al, 2003).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
“…Also, because NAA appears at low micromolar levels in cerebrospinal fluid (Faull et al, 1999), this could represent another route of NAA clearance from brain. Finally, it is possible that NAA taken up from the extracellular space by astrocytes could be transferred to oligodendrocytes via specific gap junctions (connexons) composed of connexins Cx32 and Cx47 (Menichella et al, 2003;Odermatt et al, 2003).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
“…The marked discrepancy between the devastating CNS phenotype in people with PMLD (Uhlenberg et al 2004) and the mild CNS phenotype of mice that are homozygous for a null Gja12/cx47 allele (Menichella et al 2003;Odermatt et al 2003) remains to be explained. The differences in the primary amino acid sequence of mouse and human Cx47 (Suppl.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Anatomical and functional studies of the rodent CNS have demonstrated that astrocytes and oligodendrocytes are coupled by gap junctions (Massa and Mugnaini 1982;Ransom and Kettenmann 1990;Robinson et al 1993;Rash et al 1997), and that each cell type expresses different connexins (Dermietzel et al 1989;Yamamoto et al 1990;Scherer et al 1995;Dermietzel et al 1997;Ochalski et al 1997;Nagy et al 1999;Altevogt et al 2002;Menichella et al 2003;Odermatt et al 2003;Kleopa et al 2004). Astrocyte/astrocyte (A/ A) coupling is likely mediated by Cx43/Cx43 and Cx30/Cx30 homotypic channels, and astrocyte/oligodendrocyte (A/O) coupling is most likely mediated by Cx43/Cx47 and Cx30/ Cx32 heterotypic channels, with an uncertain contribution of Cx26/Cx32 channels (Rash et al 2001;Nagy et al 2003;Altevogt and Paul 2004;Li et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of proteins important for this process, such as Kir4.1 K + channels,15, 16 glial gap‐junction proteins,17 and the astrocytic water channel aquaporin‐4 (AQP4),18 lead to impaired [K + ] o clearance and to epileptiform brain activity or an altered seizure threshold. MLC1 and GlialCAM undergo molecular interactions with several of these proteins 19, 20.…”
mentioning
confidence: 99%